Extreme Weather and Gender-Based Violence: Understanding Risks for Women and Girls (Journal of Asian Development Studies, 2025)
This study examines how extreme weather events intensify gender based-violence (GBV) against women and girls and identifies the mechanisms through which this exacerbation occurs. Drawing on an integrated theoretical framework combining ecofeminism, social learning theory, and intersectionality-vulnerability perspectives, the research addresses three objectives: assessing whether extreme weather events heighten GBV, identifying the factors driving this increase, and proposing policy responses. The study employs a systematic review and thematic analysis of literature identified through PubMed, Scopus, and Web of Science. Of 2,103 records screened, 39 studies met the inclusion criteria, capturing diverse extreme weather events, including floods, droughts, heatwaves, and wildfires and multiple forms of GBV, such as intimate partner, domestic, and sexual violence. Qualitative studies were deductively analyzed using theory-informed themes, while quantitative studies were narratively synthesized within the same analytical framework. Across the reviewed literature, 95% of studies reported a positive association between extreme weather events and increased GBV. Key drivers included infrastructure loss, displacement, resource scarcity, mental health stressors, and the reinforcement of harmful gender norms. The findings demonstrate that climate-related GBV is not an isolated consequence of disaster but a systemic outcome shaped by entrenched patriarchal structures. By integrating multi-layered theory with policy-oriented analysis, this study exposes a critical gap in current climate and public health responses. It advances actionable recommendations, including gender-responsive monitoring systems, the integration of GBV indictors into nationally determined contributions (NDCs), and targeted climate financing mechanisms to mitigate violence in disagree affected contexts.